Positive B cell flow cytometry crossmatch without detectable donor-specific antibodies: true or false reactivity? - de Chickera, Sonali N.; Al Agbar, Sabina; Sharma, Arpit; Beaune, David; Sidahmed, Eva A.; Gunaratnam, Lakshman; Sidahmed, Abubaker (Frontiers in Immunology, 2026)
In kidney transplant workups, supplementing flow cytometry crossmatches (FCXMs) with solid-phase assays (SPAs) helps differentiate between true positive from false positive results, which can prevent unnecessary waitlist delays. This study presents an analysis of three discordant cases characterized by positive B-cell FCXM results and the absence of detectable donor-specific antibodies (DSAs). Peripheral blood samples were obtained from both recipients and donors for HLA typing, FCXM, antibody screening, and surrogate crossmatches, with expanded single antigen bead assays at One Lambda laboratory to detect unidentifiable antibodies. Initial FCXM positivity did not correlate with SPA-confirmed DSAs. However, surrogate crossmatch results varied: Recipient 1 had unacceptable antigen leading to a halted transplant, Recipient 2’s negative results allowed the transplant to proceed, and Recipient 3’s mixed results led to the decision not to proceed with the transplant due to an unacceptable antigen. The findings suggest that a positive FCXM, in the absence DSAs, may be interpreted as false positive, underscoring the necessity for comprehensive testing in the pre-transplant evaluation process. Employing multiple diagnostic techniques ensures more accurate risk assessments, improves transplant outcomes, and expands the pool of suitable donors, emphasizing the critical role of thorough HLA and non-HLA antibody evaluations.